Structure pre-requisites for isoflavones as effective antibacterial agents - Mukne, Alka P.; Viswanathan, Vivek; Phadatare, Avinash G. (Pharmacognosy Reviews)
Recent reports reveal that there is increasing incidence of infections of multidrug-resistant bacteria, including methicillinresistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE). Flavonoids and related compounds have been shown to possess potent antimicrobial activities. Most of the flavonoids are considered as constitutive antimicrobial substances recently termed as “Phytoanticipins,” especially those belonging to prenylated flavonoids and isoflavones. The current review highlights the structure prerequisites for isoflavones as antibacterial agents. Structure–activity relationship (SAR) conclusions have been drawn by comparing the reported minimum inhibitory concentration values for the various isoflavones against S. aureus and MRSA. There exists a significant co-relationship between the presence of certain functional groups (prenyl group, phenolic hydroxyl) at particular positions and antibacterial activity of the compounds. These trends have been postulated with a view of assisting better drug designing of future next-generation antiinfectives, particularly against the bothersome multidrug-resistant microbes. The SAR of these isoflavones has also proved to be a basis to explore the mechanism of antibacterial action. Thus, the study would prove extremely useful to synthesize antibacterial isoflavones in future, which would eventually be beneficial for optimizing the lead molecule for the antibacterial action.
Keywords: Antibacterial activity; Isoflavones; SAR of isoflavones